Practicing of Women Reproductive Health Rights: A Road Map for HIV Prevention - Asghar, Kanwal; Maann, Ashfaq Ahmad; Zafar, Muhammad Iqbal; Ali, Tanvir (Pakistan Journal of Nutrition, 2010)
Denying of reproductive health rights encompasses the problems of HIV and STDs/STIs, unintended pregnancy and abortion and infertility. The present study was designed to identify vulnerability (towards HIV/AIDS) and violence against women due to lack of knowledge at reproductive health rights. It was found that those married women who were agreed that HIV/AIDS and STD/STIs are preventable had ‘highly consistent’ attitude towards the RHR practice. Similarly, statistically highly significant positive relationship was observed from the correlation coefficient Somers’d (p<0.0001) between the perception of married women about the RH-Security and their attitude towards the practices of RHR. It was suggested that in addition to the information that HIV/AIDS and STD/STIs are preventable diseases married women must have information and knowledge about the preventive measures. Only then they can insist for the adoption of any RH-Service to her partner or spouse.